Search for the 23/2+ isomeric state in 125 Te. (17th April 2019) - Chakraborty, S.; Sharma, H. P.; Tiwary, S. S.; Majumder, C.; Banerjee, P.; Ganguly, S.; Rai, S.; Pragati,; Mayank,; Kumar, S.; Kumar, A.; Bhattacharjee, S. S.; et al.
Abstract: Excited states in 125 Te have been populated via the 122 Sn( 9 Be, α 2 nγ ) fusion-evaporation reaction. The positive parity band has been extended up to by placing a 693 keV γ -transition. Spin and parity of several excited states have been confirmed by the present spectroscopic measurements. has been assigned to the 2569 keV state firmly, which is a possible candidate for a nanosecond isomer in the chain.